On Ekmečić’s Research Method and Understanding of the Notions of Nation and Nationalism - Aleksić, Jovan J. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
Research into the life and work of Milorad Ekmečić shows that this eminent historian dedicated a significant portion of his scholarly efforts to studying the emergence, development, aspirations, and goals of the South Slavs’ national revival. In accordance with the Western European historiographical tradition, he often referred to this as “nationalism.” Ekmečić’s research interest in various aspects of the topic can be traced back to the early days of his academic career. Over the years, with accumulated experience, he delved deeper into the subject, approached it from various angles, and examined it from multiple perspectives. In his research, he acted not only as a historian of the past but also as an analyst of ideas and a philosopher of history. His insights into the origins, definitions, interpretations, and evolution of the concept of nation and nationalism significantly contributed to the study of this subject.